Strategi Kepala Sekolah Dalam Memajukan Lembaga Pendidikan Islam di Pedesaan: Studi Kasus di MTS Negeri 3 Aceh Jaya - M, Musliadi; Usman, Fadly (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research examines the strategies of school principals in promoting Islamic education institutions in rural areas with a focus on MTs State 3 Aceh Jaya Krueng Sabee District, Aceh Jaya Regency. The purpose of the study was to explore the strategic measures taken in improving the quality of education in neighborhoods facing various challenges post-tsunami 2004. The research method employed a qualitative approach with data collection techniques through observation, in-depth interviews, and study of documents. Data analysis was performed by data reduction, data display, and conclusion drawing. The results of the study showed that the strategies applied included curriculum adjustment to local culture, development of teachers’ professionalism through training, as well as improvement of educational facilities. The impact of this strategy is evident in an increase in student enrollment by up to 30% and more active community participation in educational activities. Supporting factors include community support and strong leadership, whereas hindering factors include proximity to facilities and access to quality training. This study makes an important contribution in understanding the dynamics of educational leadership in rural areas and provides practical recommendations for sustainable quality improvement of Islamic education.